Hubungan Stunting dengan Kejadian Karies Gigi pada Anak di Kecamatan Sungai Kunjang Samarinda: The Relationship Between Stunting and the Incidence of Dental Caries in Children in Sungai Kunjang District, Samarinda - Damayanti, Desty Tri; Hanan, Nydia; Ompusunggu, Novelin Yohana; Hasanah, Nurul; Cahya, Wahyuni Dwi (ITKES Wiyata Husada Samarinda, 2024)
Stunting is a common malnutrition condition. Stunting conditions can disrupt children's development, including developmental disorders in the oral cavity. Children with stunting are more susceptible to dental caries due to changes in saliva characteristics. The aim of this research is to determine the relationship between stunting and the incidence of dental caries in children in Sungai Kunjang District. This research is a descriptive analytical study that uses a cross-sectional design with saturated sampling techniques. The research respondents were 20 elementary school children who experienced stunting and were recorded by the community health center in Sungai Kunjang District. The research was carried out by intraoral examination of the respondents' oral cavities and checking students' health report books. Research data was processed and analyzed using the Chi-square test. The research results showed that all children with stunting had caries on their teeth with a DEF-T index of 4.95 (high). The results of statistical tests on the relationship between stunting and the incidence of caries show p = 0.000 (p < 0.05), indicating that there is a relationship between stunting and the incidence of dental caries in elementary school children in Sungai Kunjang District.